Peran Kebijakan Sumber Daya Alam dalam Mewujudkan Transisi Energi berbasis Green Hydrogen di Indonesia: Penelitian - Bonaraja Purba; Ainun Saskia; Essi Laura Amanda; Rachel Adeline Siagian; Afriyani Elizabet Sitorus (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The transition toward clean energy poses a major challenge for Indonesia due to its high dependence on fossil fuels. Green hydrogen is considered a strategic option to strengthen energy security while supporting the national decarbonization agenda. This study aims to analyze the role of natural resource management policies in driving the energy transition based on green hydrogen in Indonesia. The research employs a literature review with a descriptive qualitative approach through the examination of academic journals, international institutional reports, and official government documents. The findings reveal that although Indonesia possesses abundant renewable energy potential, the implementation of green hydrogen remains constrained by high production costs, limited infrastructure, and the absence of comprehensive regulations. Natural resource policies play a strategic role in overcoming these barriers through regulatory support, fiscal incentives, infrastructure development, and integration with low-carbon development strategies. Lessons from Japan and Germany highlight the importance of policy consistency, sustainable financing, and cross-sectoral coordination. Comprehensive and adaptive natural resource policies are the key to accelerating the green hydrogen–based energy transition. This study emphasizes that such policies are not merely technical instruments, but also strategic foundations for strengthening energy security, fostering a green economy, and ensuring sustainable national development.